Learning Approach in Madrasah Institutions in Indonesia - Suharyat, Yayat; Hambali, Imam (International Journal of Global Sustainable Research, 2023)
Madrasahs have a strategic role in nation building. Madrasah is still considered number two because the implementation of madrasah still faces major problems such as management problems and low quality of madrasah education. In its development, there were two momentums for the existence of madrasahs, namely SKB 3 ministers 1975 which became the beginning of a recognition of madrasah as an Islamic educational institution equivalent to general education. National Education System Law Number 2/1989 which makes madrasah not only an educational institution equivalent to the public, but also madrasah is recognized as a public school. The emergence of SKB 3 ministers is considered a positive step for improving the quality of madrasahs. the value of the diploma and the curriculum.  The development of the madrasah curriculum is inseparable from the beginning of converting to Islam and its development since the pre-independence era until now. Broadly speaking, the madrasah curriculum is divided into three periods, namely: the madrasah curriculum before independence, the madrasah curriculum after independence, the madrasah curriculum after independence. The curriculum in its transformation undergoes changes for education in the future and develops in accordance with the needs and developments of the times until it can become the curriculum it is today. With the curriculum, learning is more structured and directed.